1990
DOI: 10.1111/j.1528-1157.1990.tb05371.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosinergic Modulation of Homocysteine‐Induced Seizures in Mice

Abstract: Homocysteine thiolactone (HTL) elicits seizures in mice at a dose of 850 mg/kg (95-100% of animals) with an average latency time of 19.5 min. These seizures are reversed by both 5' N-ethylcarboximide adenosine (NECA) and flunitrazepam, with respective ED50 doses of 0.025 and 0.20 mg/kg. NECA was approximately four-fold more potent as an inhibitor of HTL-induced seizures than of seizures induced by pentylenetetrazol (PTZ, 75 mg/kg). Flunitrazepam was equipotent in both seizure paradigms. The purine precursor 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 19 publications
2
38
0
1
Order By: Relevance
“…These antiplatelet effects of acadesine were prevented by pretreatment with the adenosine receptor antagonist, 8-SPT, at a dose that abolished the coronary vasodilator response to adenosine but did not block the antiplatelet activity of aspirin. In the absence of evidence for direct binding of acadesine to adenosine receptors (39), these data support the in vitro results demonstrating an adenosine-mediated action of acadesine.…”
Section: Discussionsupporting
confidence: 78%
“…These antiplatelet effects of acadesine were prevented by pretreatment with the adenosine receptor antagonist, 8-SPT, at a dose that abolished the coronary vasodilator response to adenosine but did not block the antiplatelet activity of aspirin. In the absence of evidence for direct binding of acadesine to adenosine receptors (39), these data support the in vitro results demonstrating an adenosine-mediated action of acadesine.…”
Section: Discussionsupporting
confidence: 78%
“…The beneficial effects of systemic AICAR administration may be mediated by peripheral tissue, such as muscle tissue, and systemic AICAR administration is not beneficial for behavioral performance or neural plasticity in the absence of the muscle expression of AMPK, and oral AICAR administration is sufficient to increase running endurance by nearly 45% in sedentary mice (Narkar et al, 2008). In addition, o1% of AICAR is able to permeate the blood-brain barrier (Marangos et al, 1990), suggesting that the effects of systemic AICAR administration on the formation of spatial memory are likely indirect. Using a classical fear conditioning model, we found that increasing AMPK activity in the CA1 impaired the formation of longterm fear memory.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since AICAR is not able to effectively cross the blood-brain barrier (Marangos et al, 1990), this increase in hypothalamic AMPK activity may represent a compensatory response to AICAR-induced reductions in blood glucose.…”
Section: Discussionmentioning
confidence: 99%